Rewitalizacja środowiska zurbanizowanego w procesie kształcenia studentów architektury na Politechnice Łódzkiej na przykładzie wybranych międzynarodowych warsztatów - Walczak, Bartosz, M. (Lodz University of Technology Press, 2016)
An Urban regeneration is one of the crucial challenges of contemporary post-industrial societies. It is predominantly due to dynamic nature of social and economical transformation of a global dimension, described by Alvin Toffler as “the third wave”. Such a situation calls for well-trained specialists. Polish universities are however able to prepare future architects for participation in regeneration processes only to a limited extent. A solution filling this gap – at least to some degree – organisation of workshops, especially those of international range. There have been described workshops co-organised by the Institute of Architecture and urban Planning of the Lodz University of Technology over last decade (including those in Berlin, Cottbus, Mainz and – of course – Lodz). Based on the experience from these projects it is perfectly possible to indicate that they have appeared to be an effective teaching method, in line with contemporary trends in the didactic process, such us problem based learning. The experience gained by participating students is a valuable supplement to the regular course of studies. What is more, it is essential for their future careers as architects and urban designers, since they will be well prepared for co-operation in interdisciplinary teams responsible for planning and implementing regeneration processes. Concurrently, the workshops results are a valuable auxiliary material for local authorities – being usually among their organisers – in solving current urban renewal problems.
Urban regeneration in the education process of students of architecture at the Lodz University of Technology as exemplified by international workshops
Keywords: revitalization urbanized areas; revitalization process; rewitalizacja obszarów zurbanizowanych; proces rewitalizacji